A case-control study to investigate the relation between low and moderate levels of physical activity and osteoarthritis of the knee using data collected as part of the Allied Dunbar National Fitness Survey. Issue 8 (1st August 2001) - Sutton, A J; Muir, K R; Mockett, S; Fentem, P
Abstract : BACKGROUND: Physical activity is being recommended as an intervention for seemingly almost universal improvements to health. A potential concern with this recommendation for increased exercise is that some believe increased levels of activity may lead to increased incidence of osteoarthritis of the knee (knee OA), as a result of accelerated "wear and tear" of the major joints. OBJECTIVE: To investigate the hypothesis that the occurrence of knee OA may be related to the duration of participation in some forms of sport and active recreation. METHODS: The relation between habitual exercise, reported by a cross section of people surveyed in England, and self reported knee OA was investigated. Data were derived from the Allied Dunbar National Fitness Survey (1990–91). A matched retrospective case-control design was used and a new exposure classification system which categorised different grades of activities for different time periods for each subject's lifetime participation in regular physical activities was developed. Additional data on knee injuries sustained and bodily composition were also included in a multivariate analysis. RESULTS: From 4316 people originally interviewed, 216 eligible cases (66 men, 150 women) were identified (mean age 57.1). Each case was matched to four controls. When habitual sport/exercise participation were examined during a subject's life, only exposure to regular long walks and being physically active between the ages of 20 and 24 suggested any association with developing knee OA later in life. The only strong association found was a greatly increased risk of knee OA having previously sustained a knee injury (p<0.01, odds ratio 8.0 (95% confidence interval 2.0 to 32.0)). CONCLUSIONS: There was little evidence to suggest that increased levels of regular physical activity throughout life lead to an increased risk of knee OA later in life. Previous knee injury was associated with an increased risk of knee OA. Additionally, most injuries were caused through participation in physical activities. Hence, when deciding on participation in activities, it is worth taking the likelihood of joint injury into consideration, as the chance of injury is greater in some activities than others.